2019
DOI: 10.1038/s41598-019-39744-8
|View full text |Cite
|
Sign up to set email alerts
|

Wavelength-dependent Optical Instability Mechanisms and Decay Kinetics in Amorphous Oxide Thin-Film Devices

Abstract: We present a study on decay kinetics for a recovery process depending on the light wavelength selected in optical instability measurements against amorphous In-Ga-Zn-O (a-IGZO) thin-film devices. To quantitatively analyze optically-induced instability behaviors, a stretched exponential function (SEF) and its inverse Laplace transform are employed for a time- and energy-dependent analysis, respectively. The analyzed results indicate that a shorter wavelength light activates electrons largely from the valence ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…For this same system, it was found that the photoconductivity has a strong correlation with the field effect mobility (µ FE ) and hence with the thin film transistor (TFT) performance [129]. Very recently, a study on decay kinetics for In-Ga-Zn-O (a-IGZO) thin-film devices has been proposed [130]. The stretched exponential function and its inverse Laplace transform were employed for a time-and energy-dependent analysis, respectively.…”
Section: Other Interesting Structures That Present Some Sort Of Condu...mentioning
confidence: 99%
“…For this same system, it was found that the photoconductivity has a strong correlation with the field effect mobility (µ FE ) and hence with the thin film transistor (TFT) performance [129]. Very recently, a study on decay kinetics for In-Ga-Zn-O (a-IGZO) thin-film devices has been proposed [130]. The stretched exponential function and its inverse Laplace transform were employed for a time-and energy-dependent analysis, respectively.…”
Section: Other Interesting Structures That Present Some Sort Of Condu...mentioning
confidence: 99%
“…Most notably, lamp-based optical illumination methods performed on a-IGZO TFTs, such as photoexcitation charge collection spectroscopy (PECCS) [24], have been successful in quantifying the density of defect states in the subgap. TFT behavior under illumination has also been shown to depend strongly on photon energy (hν), especially upon photoexcitation of "deep states" near the valence band [25][26][27][28], which suggests the existence of multiple species of subgap states. However, the near-band-gap photoexcited TFT behavior has been multiply attributed to defects related to hydrogen [29][30][31], excess oxygen [32][33][34], and, contradictorily, the lack of oxygen [35].…”
Section: Introductionmentioning
confidence: 99%
“…In general, in oxide semiconductors, V o provides electrons inside the thin film 16 . However, the optimization of the mobility enhancement and the stability is an important issue because V o can also act as defected states 24,25 . Therefore, from Fig.…”
Section: Resultsmentioning
confidence: 99%